The Spiderwick Chronicles: Lucinda's Secret - Book 3 - DiTerlizzi, Tony; Black, Holly (New York : Simon & Schuster Books for Young Readers, 2003)
With goblins, trolls, and the house boggart all trying to get them, the Grace children turn to Great Aunt Lucinda for help.
Sequel to: The seeing stone.
Keywords: Brothers and sisters -- Fiction; Great-aunts -- Fiction; Supernatural -- Fiction